Popular Education: A collective construction from the South and bottom up - Mejia J., Marco Raúl (Education Policy Analysis Archives, 2014)
The present article is about the maturity of popular education. By tracing its historical, conceptual, and methodological development, it shows its accumulated experience and the way it collects the most diverse Latin American critical traditions -- and also from other continents--, to give shape to an educational and pedagogical proposal for all of society and educators committed to build a fairer society without differences that exclude. In this sense, alternative groups are seeking to educate human beings who are to build on their different social milieus respect for differences, unveiling of inequality and inequity, and are willing to reestablish democracy from local identities and, in this text, from the South. In this perspective, the text shows those conceptual, social and practical axes on which popular education builds its force in the 21st century and gives answers from their built projects to shape a political and pedagogical proposal in a context of cognitive capitalism and neoliberal globalization.